Changes in relationships, HIV risk, and feelings towards PrEP: findings from a qualitative explanatory study among participants in the CHARISMA intervention trial - Miriam Hartmann; Noah Triplett; Sarah T. Roberts; Michele Lanham; Krishnaveni Reddy; Siyanda Tenza; Nonkululeko Mayisela; Dorica Mbewe; Ontathile Maboa; Lydia Mampuru; Elizabeth E. Tolley; Thesla Palanee-Phillips; et al. (BMC, 2023)
Abstract Background Intimate partner violence (IPV) and other relationship-based challenges have been demonstrated to reduce women's ability to use pre-exposure prophylaxis (PrEP) effectively for HIV prevention. The Community Health Clinical Model for Agency in Relationships and Safer Microbicide Adherence (CHARISMA) intervention was designed to mitigate these challenges and increase South African women's agency to use PrEP. The CHARISMA randomized controlled trial did not identify statistically significant differences in PrEP adherence or relationship dynamics between the intervention and control arms. As such, the aim of this explanatory qualitative sub-study was to understand women's experiences with the CHARISMA trial and explore reasons for the null results. Methods Twelve CHARISMA trial participants were purposively selected to participate in serial in-depth interviews, which took place at the trial end and 3 months later. Participants represented individuals who had received each of the three counselling modules, 1) healthy communication counselling, 2) PrEP disclosure counselling, or 3) IPV counselling, as well as those in the control arm who received IPV standard-of-care counselling. Results A thematic case analysis revealed numerous positive relationship outcomes among intervention participants, including identifying and ending unhealthy relationships, gaining a sense of personal empowerment, and enacting more positive behaviors and HIV risk reduction strategies in subsequent relationships. These positive shifts were occasionally described as contributing to decisions to discontinue PrEP use, which may partly explain the limited impact of the intervention on PrEP adherence. Conclusions Future investigations of counselling interventions addressing relationship-based barriers to PrEP use should account for changing risk dynamics and need for PrEP.